Tecnologia da informação e competitividade no Setor Bancário - Carvalho, Isabel Cristina Monteiro de (2002)
Information Technology (IT) has been incorporated into modern society that is modifying organizations, and the way products and services are created and offered to the population. The Brazilian Banking Industry has been investing in IT since the Sixties and was one of the first Economic sectors to open this technology to the general public in dealing with its customers and its internal activities. There fore this study has been conducted on The Banking Industry with the objective of identifying and analyzing how Information Technology influenced Brazilian Banks in the processes of modernizing its structures. This dissertation is in four parts: The first two chapters study the role of competition and technology; while the last two chapters utilize data from several sources, like: FEBRABAN, newspaper articles and other publications, to determine how IT was inserted into the new competitive strategies of banks adopted since the Eighties in comparison between Brazilian and United States of Américan banks (where focused the main instrument were used by banks inside this process)